2014
DOI: 10.1016/j.schres.2014.01.016
|View full text |Cite
|
Sign up to set email alerts
|

d-Cycloserine augmentation of cognitive remediation in schizophrenia

Abstract: D-cycloserine (DCS) has been shown to enhance memory and, in a previous trial, once-weekly DCS improved negative symptoms in schizophrenia subjects. We hypothesized that DCS combined with a cognitive remediation (CR) program would improve memory of a practiced auditory discrimination task and that gains would generalize to performance on unpracticed cognitive tasks. Stable, medicated adult schizophrenia outpatients participated in the Brain Fitness CR program 3–5 times per week for 8 weeks. Subjects were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
47
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 58 publications
2
47
0
3
Order By: Relevance
“…This framework suggests that, given the minimum NMDAR activation necessary to produce transient, persistent firing, further NMDAR activation should have relatively limited effect on working memory performance. Our finding of similar working memory performance between DCS and Placebo participants is consistent with this theory and is in line with prior studies that failed to find effects of DCS on working memory in healthy volunteers or patient groups (27,(34)(35)(36). This dissociation of effects of DCS on experience-dependent learning versus working memory highlights the importance of considering the cellular mechanisms underlying distinct cognitive functions and demonstrates how investigating targeted hypotheses that capitalize on basic cognitive neuroscience can help reconcile discrepant effects of potential cognitive-enhancing drugs.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This framework suggests that, given the minimum NMDAR activation necessary to produce transient, persistent firing, further NMDAR activation should have relatively limited effect on working memory performance. Our finding of similar working memory performance between DCS and Placebo participants is consistent with this theory and is in line with prior studies that failed to find effects of DCS on working memory in healthy volunteers or patient groups (27,(34)(35)(36). This dissociation of effects of DCS on experience-dependent learning versus working memory highlights the importance of considering the cellular mechanisms underlying distinct cognitive functions and demonstrates how investigating targeted hypotheses that capitalize on basic cognitive neuroscience can help reconcile discrepant effects of potential cognitive-enhancing drugs.…”
Section: Discussionsupporting
confidence: 92%
“…These findings suggest exciting possibilities for using NMDAR agonists to help ameliorate plasticity deficits in neurodegenerative and psychiatric disorders. Our results complement a growing literature that suggests that DCS can enhance new learning during CBT interventions (29,32) and cognitive training programs (33,34). The dissociation of effects of DCS on incremental learning versus working memory highlights the importance of capitalizing on progress in basic cognitive neuroscience to develop more specific hypotheses for targets of cognitive-enhancing drugs.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…One recent study found that DCS improved performance on an auditory discrimination task on which patients were trained over 8 weeks. 68 However, numerous studies found minimal effects of DCS on neuropsychological tests of short-term verbal or spatial learning in schizophrenia patients. [61][62][63]68 Given that we did not measure NMDAR signaling or synaptic changes directly in the current study, any mechanistic explanations for our negative findings of DCS on plasticity in schizophrenia are speculative.…”
Section: Discussionmentioning
confidence: 99%
“…68 However, numerous studies found minimal effects of DCS on neuropsychological tests of short-term verbal or spatial learning in schizophrenia patients. [61][62][63]68 Given that we did not measure NMDAR signaling or synaptic changes directly in the current study, any mechanistic explanations for our negative findings of DCS on plasticity in schizophrenia are speculative. However, the minimal effects of DCS on plasticity in the current study could reflect a breakdown in the translation of electrical signaling across the NMDAR into the signaling cascades and synaptic changes that underlie experience-dependent plasticity.…”
Section: Discussionmentioning
confidence: 99%